Methods to evaluate driving competence for people with acquired brain injury (ABI): A systematic review - Doha Alhashmi; Doha Alhashmi; Aislinn Lalor; Aislinn Lalor; Ellie Fossey; Ellie Fossey (Frontiers Media S.A., 2023)
Driving is essential for independence, community involvement and quality of life. Driving is the primary transportation method in Saudi Arabia. Despite the high rates of brain injuries and disability in Saudi Arabia, currently there are no guidelines regarding driver assessment and rehabilitation to facilitate people with brain injuries to resume driving. Therefore, this systematic review aimed to understand the assessment methods used internationally to evaluate driving competence for people with acquired brain injuries (ABI). A systematic search of six electronic databases was conducted by two authors and twenty-six studies were identified for review. Four main approaches to driver assessment: clinical assessments such as neuropsychological tests, off-road screening tools, simulator testing, and comprehensive driving assessment were identified. However, our findings revealed a lack of consistency in their use to assess driving competence after ABI. On-road driving performance tests were predominantly used to determine driving competence either independently or in combination with another method in over two-thirds of the reviewed studies. While clinical assessments of cognitive impairments showed some capacity to predict driving performance of people with ABI, they should be used with caution since they cannot replace on-road driving performance tests. Driver assessment should be part of rehabilitation following high prevalence conditions such as ABI. This systematic review offers guidance for Saudi clinicians, as well as policymakers, about providing rehabilitation services for people with ABI, and recommendations for further research and collaborations to improve this much-needed area of practice.